Answer:
The scale factor is the ratio of the length of a side of one figure to the length of the corresponding side of the other figure.
Step-by-step explanation:
Answer:
x = -3
General Formulas and Concepts:
<u>Pre-Algebra</u>
- Order of Operations: BPEMDAS
- Equality Properties
Step-by-step explanation:
<u>Step 1: Define equation</u>
5(x + 4) = -2(-4 - x) + 3
<u>Step 2: Solve for </u><em><u>x</u></em>
- Distribute: 5x + 20 = 8 + 2x + 3
- Combine like terms: 5x + 20 = 2x + 11
- Subtract 2x on both sides: 3x + 20 = 11
- Subtract 20 on both sides: 3x = -9
- Divide 3 on both sides: x = -3
<u>Step 3: Check</u>
<em>Plug in x to verify it's a solution.</em>
- Substitute: 5(-3 + 4) = -2(-4 - -3) + 3
- Simplify: 5(-3 + 4) = -2(-4 + 3) + 3
- Add: 5(1) = -2(-1) + 3
- Multiply: 5 = 2 + 3
- Add: 5 = 5
Here we see that 5 does indeed equal 5. ∴ x = -3 is a solution of the equation.
And we have our final answer!
The given equation -2(11 - 12x) = -4(1 - 6x) has infinite solutions
<u><em>Solution:</em></u>
Given that we have to solve the given expression
Given expression is:
-2(11 - 12x) = -4(1- 6x)
We have to use distributive property to solve the given expression
The distributive property lets you multiply a sum by multiplying each addend separately and then add the products.
Which means,
a(b + c) = ab + ac
Apply this in given expression
-2(11 - 12x) = -4(1-6x)
-22 + 24x = -4 + 24x
When both sides of the equation are simplified, the coefficients are the same, then infinite number of solutions occur
If we end up with the same term on both sides of the equal sign, such as 24x = 24x, then we have infinite solutions
Y=$175+x I think this is it? one half of 175 is 87.5 so you know.
Answer:
0.2 repeating
Step-by-step explanation: